LC–HRMS Metabolomics Fingerprints and Pathway Signatures Authenticate Geographic Origin of Pempek (Channa striata) - Ridhowati, Sherly; Lestari, Shanti Dwita; Saputra, Daniel; Wulandari, Wulandari; Wulandari, Diah Anggraini; Nurhasanah, Siti; Supriadi, Agus (Trends in Sciences, 2026)
This study demonstrates that non‑targeted liquid chromatography–high‑resolution mass spectrometry (LC–HRMS) metabolomics provides a robust framework for authenticating the geographic origin of pempek, a traditional fish‑based food prepared from Channa striata. The work addresses the limited application of untargeted LC–HRMS to processed freshwater fish products across multiple regions by explicitly testing whether molecular fingerprints capture ecological and artisanal differences between Jambi and South Sumatra. Samples were processed under standardized protocols and analyzed with LC–HRMS, followed by variance stabilization and chemometric modeling in MetaboAnalyst (a web-based platform for metabolomics data analysis). Principal component analysis (PCA) revealed origin‑based clustering, and orthogonal projections to latent structures–discriminant analysis (OPLS-DA), supported by extensive permutation validation, confirmed significant separation. Discriminatory metabolites included carnitines, choline, and creatinine enriched in Jambi products, contrasted with ether‑linked phosphatidylcholines and sphingomyelins enriched in South Sumatra products. Pathway enrichment analyses linked these differences to membrane lipid biosynthesis and fatty‑acid beta‑oxidation, while receiver operating characteristic (ROC) curves based on a multi‑marker panel demonstrated near‑perfect discrimination. These findings indicate that both endogenous metabolic traits and exogenous processing signatures jointly shape pempek metabolomes. The study advances food authenticity science by moving beyond descriptive profiling toward mechanistic interpretation and translational application. By establishing evidence‑based fingerprints for pempek, it provides a scientific foundation for protecting the cultural and economic value of this traditional Indonesian food. Future directions should include cross‑season and interlaboratory validation, targeted assays with authentic standards, and expanded regional comparisons to strengthen regulatory translation and consumer trust. HIGHLIGHTS LC–HRMS fingerprints distinguish pempek origins (Jambi vs. South Sumatra) Chemometric modeling (PCA, OPLS-DA, ROC) ensures robust authentication. Key markers: carnitine, choline (Jambi) vs. phosphatidylcholines (South Sumatra) Pathway enrichment links origin to lipid and energy metabolism differences Validated marker panel enables accurate and culturally significant authentication GRAPHICAL ABSTRACT